Application of Group Type Learning Model Investigation of Capabilities Mathematical Communication - Zuhri Zuhri; Irwan Irwan; Ismail Ismail; Hidayat Hidayat; Rahmadani Hasibuan (International Journal of Social Service and Research, 2023)
This research was conducted to determine the increase in the mathematical communication skills of class XI students at Tamansiswa Private Vocational School, Padang Tualang Branch, for the 2020/2021 academic year, which was taught using the group investigation learning model. In this study using the type of experimental research with data analysis techniques that are processed quantitatively. This research was conducted at the Tamansiswa Private Vocational School, Padang Tualang Branch. The samples used in this study were 2 classes among 3 classes, namely class XI TKRO-1 as the control class and XI TKRO-2 as the experimental class, each of which used SPSS Version 20. Before testing the hypothesis, the validity and reliability instruments were first tested. , it is known that the data is valid and reliable and the n-gain test is carried out then the normality and homogeneity tests are carried out. The n-gain values ??for students' mathematical communication skills for the experimental class and the control class are 5.5 and 2.1 and based on the calculations, the significance is 0.000 <0.05. Which means that there is an influence or significant increase in the results of students' mathematical communication abilities that have been applied between the group investigation learning model and conventional learning methods.